A Deteksi Kekurangan Pelumas Bearing untuk Mencegah Kerusakan pada Motor Induksi Kompresor Udara - Cachandra, Varel Farhan; Farhan, Varel; Irianto, Chairul Gagarin; Kasim, Ishak; Sari, Tyas Kartika (Jetri : Jurnal Ilmiah Teknik Elektro, 2023)
The induction motor is one of the most important parts in the industrial world today, so if an induction motor is damaged it can affect the production process. Therefore, disturbances that exist in induction motors must be predicted or detected as early as possible. One of the causes of bearing damage is lack of lubrication which can cause an increase in motor temperature, noise, vibration and sparks which can cause damage to other parts of the induction motor. So the authors will conduct research using four different parameters namely starting current, vibration, and temperature on Air Compressor motors whose maintenance treatment in re-lubrication is carried out differently. In this study it was found that if the lubrication on the bearings is not maintained properly then the vibration value is very high at 23 to 24 mm/s, the starting current itself increases up to 8 times the nominal current where this can cause large voltage losses, the current is above the nominal current of the motor, which is 133% of the nominal current, with dry lubrication on the bearings of the induction motor, friction cannot be minimized so that the temperature of the motor increases where data is obtained on the temperature rise of the induction motor for 5 minutes the motor works at 74.3⁰ C and this can endanger the induction motor itself, it can be concluded that the lack of lubrication on induction motor bearings affects 4 parameters mentioned before. Keywords: 3 phase induction motor, Air Compressor, Bearing, Lubrication Oil, Vibration